The technology factors as barriers for sustainable Health Information Systems (HIS) – a review - Mohamadali, Noor Azizah; Ab Aziz, Nur Faizah (Elsevier, 2017)
Information system is widely adopted in many fields including healthcare. Healthcare organizations now consider increased efficiency, improved patient care, quality of services, and safety. Hence Health Information System (HIS) is basically introduced to transform the traditional way of data collection and organization in hospitals, to a modern way of systematic collection, maintaining and dissemination of data. Its implementation is to support medical practitioners and administrative staff in securing patients’ health information in a digital-based record, to efficiently and effectively improve performance in the health system or any of its component parts. However, despite its numerous benefits, some of barriers still hinder its successful implementation and adoption, which needs to be addressed. This study discussed these barriers related to technology using the IS Success Model. This review paper becomes necessary in order to highlight the barriers that led to technical difficulties facing HIS implementation in hospitals, so as to suggest possible solutions that will improve services rendered in health industry based on findings